Are Transplant Centers That Meet Insurer Minimum Volume Requirements Better Quality?. (October 2021) - Nicholas, Lauren Hersch; Stith, Sarah See
A pervasive viewpoint in health care is that higher patient volume leads to better outcomes, implying that facility volume can be used to identify high-quality providers. Hundreds of studies documenting a positive correlation between hospital volume and patient survival have motivated payers to use arbitrary minimum volume standards for elective surgical procedures, though it is unknown whether these policies actually improve patient outcomes. Using an instrumental variables approach, we show that minimum volume requirements in kidney transplantation do not reduce posttransplant mortality. These results suggest minimum volume requirements are not a useful proxy measure for quality and that restricting the number of hospitals from which patients can receive care could reduce access to necessary health care services.